Evaluation of treatment related fear using a newly developed fear scale for children: "Fear assessment picture scale" and its association with physiological response - Nishidha Tiwari; Shilpi Tiwari; Ruchi Thakur; Nikita Agrawal; N D Shashikiran; Shilpy Singla (Wolters Kluwer Medknow Publications, 2015)
Introduction: Dental treatment is usually a poignant phenomenon for children. Projective scales are preferred over psychometric scales to recognize it, and to obtain the self-report from children. Aims: The aims were to evaluate treatment related fear using a newly developed fear scale for children, fear assessment picture scale (FAPS), and anxiety with colored version of modified facial affective scale (MFAS) - three faces along with physiologic responses (pulse rate and oxygen saturation) obtained by pulse oximeter before and during pulpectomy procedure. Settings and Design: Total, 60 children of age 6-8 years who were visiting the dental hospital for the first time and needed pulpectomy treatment were selected. Children selected were of sound physical, physiological, and mental condition. Two projective scales were used; one to assess fear - FAPS and to assess anxiety - colored version of MFAS - three faces. These were co-related with the physiological responses (oxygen saturation and pulse rate) of children obtained by pulse oximeter before and during the pulpectomy procedure. Statistical Analysis Used: Shapiro-Wilk test, McNemar's test, Wilcoxon signed ranks test, Kruskal-Wallis test, Mann-Whitney test were applied in the study. Results: The physiological responses showed association with FAPS and MFAS though not significant. However, oxygen saturation with MFAS showed a significant change between "no anxiety" and "some anxiety" as quantified by Kruskal-Wallis test value 6.287, P = 0.043 (<0.05) before pulpectomy procedure. Conclusions: The FAPS can prove to be a pragmatic tool in spotting the fear among young children. This test is easy and fast to apply on children and reduces the chair-side time.